Engaging homeless service providers in educational efforts during a tuberculosis outbreak in Atlanta - Preetha Nandi; Mary Worrell; Tom Andrews; Rose-Marie Sales; Jeff McMichael; Kristen Hamptom; Neela Goswami (Georgia Southern University, 2016)
Background: During an outbreak of tuberculosis (TB) in the homeless population of metropolitan Atlanta, education of homeless service providers (HSPs) about the implementation of local infection control measures was imperative to limiting the spread of TB and to preventing future outbreaks. Methods: By use of educational sessions and teaching posters, two interventions were designed to focus educational efforts from November 2014 to August 2015: 1) a spatially-targeted approach that identified HSPs within an area of Fulton County, GA (which includes downtown Atlanta) with high TB case density (cases per square mile) from 2009 - 2014, and 2) an organizational meeting approach that included scheduled meetings of professionals who had regular contact with homeless individuals at risk of TB infection. Results: Of the 18 HSPs targeted in the identified high-TB density area, 9 engaged in educational activities, and 9 were closed at time of contact or unreachable by email or phone. Through organizational meetings, 36 additional facilities were reached. Conclusions: The HSPs with successful contact were amenable to educational efforts, and a combination of spatially targeted and organizational meeting approaches with teaching aids was feasible in developing sustainable TB educational programs in the homeless community